Live tracking of saline for betterment of patient - Sayli Anand Zende; Tanvi Kulkarni; Shubhada Yadav; Ajay Biradar; Avinash Devare (Institute of Advanced Engineering and Science, 2020)
In hospitals, Saline is fed to patients to treat dehydration and use of saline improves their health. In current health care measures, whenever a saline is fed to any patient, the patient must be continuously monitored by nurse, doctor or caretaker. So basically, in all the hospitals nurse or caretaker is responsible for monitoring of saline. Due to the avoidance of nurses towards the saline level monitoring or lack of knowledge it can harm to the patients health. Therefore, to stop the patient from obtaining injured and shield their lives throughout saline feeding amount, the saline level observance system are developed. The planned system is made Internet web of Things (IoT) platform. The planned system includes of devices which can act as tier sensor for observance the crucial level of the saline within the saline bottle. Whenever the amount of the saline reaches to the predefined crucial level, then the nurses, caretaker, doctors are alerted through the alarm associate in Nursing an alert message are sent through the utilization of web to the involved nurses and doctors that there's a requirement for replacement of the saline bottle. This planned system may be utilized efficiently in homes as well as hospitals.